ANALISIS PROFITABILITAS EKlJITAS KOPERASI DI KOTA SURABAYA - Ady Soejoto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2004)
The focus of this research was the change of profitability of co-operation equity in Suarabaya. The samples amount were 175 from 318 primary cooperative which were the annual meeting members. The data were collected from book years 1998 to 2002. That were the responsibility report of it’s official member about the cooperative movement. The result of this research indicated that the influence of change of principle deposit, obligatory deposit, debt and reserve to change of co-operation equity profitability were significant. The dominant contribution was the change of deposit obligatory, flollowed by the change of reserce. The prediction of net income toward the change of capital structure of equity especially change tha internal expenditure of co-opertion. It’s dominant change toward the obligatory daposit sharpen the co-operation character, that member were the owner of client and capital.The .fhcus '?f' this research was the change <f rm?filahility <?f' co-operation equity in Surabaya. The samples amount were 175from J /H primary cooperative which were the annual meeting members. The data were collected from hook years 199H to 2002, Jhat were the responsibility report <?/'it's <?f/icial memher ahout the cooperalié movement. The result of this research indicated that the in.fluence <?f' change of principle deposit, obligatory deposit, deht a11d reseri·e to change < t' co-operation equi y pr<?fitability were significant. The dominant contribution was the change <?(deposit ohligatory, followed by the change ,4·reseri·e. The prediction <?f' net income toward the change of capital structure of equi v especially chmwe the internal expenditure <?l co-operation. lt 's dominant change tmrard the obligatory deposit sharpen the co-operation character, that member were the owner <f client and capital